Seasonal Variation of Springwater In-Situ Parameters in the Bhusundi Catchment, Gorkha, Nepal - Pokhrel, Gunanidhi; Rijal, Moti Lal (Journal of Institute of Science and Technology, 2020)
Spring is a concentrate flow of groundwater that appears at the earth’s surface. The seasonal variations of spring water quantity and quality are required to ensure water availability during the dry season. The research focuses on the seasonal variations of spring water quantity and quality with the spatial distribution of springs interlinking with geological settings of the area. Research framework has been established comprising spring inventories before and after the monsoon in 2017 AD of the Bhusundi catchment of the Gorkha district. The study area comprises phyllite and schist rocks of metamorphic origins as well as Nepheline Syenite of igneous origin. A total of 44 perennial springs along with the geological settings of the various springs were investigated for spring in-situ spring water parameters including spring discharge, electrical conductivity (EC), and total dissolved solids (TDS). The variations of spring discharge, EC and TDS ranged from 0.16 lpm-62.7 lpm, 24.4-308.0 μS/cm and 14.74-199.00 ppm, respectively, in the study area. Metamorphic rocks of this area were developed secondary porosity creating interconnectivity of these pores and hence creating suitable conditions for spring occurrences. Seasonal variations of spring water quality and quantity provide good insights increasing the water security of local communities in the hilly region. Spring inventory along with their seasonal variability provides information for increasing water security of poor and marginalized people living in the scattered settlements of hilly regions of Nepal.